Impact Response of Dam Affected by Landslide Surge Based on Improved SPH Method - Shuai HUANG; Zhonggen WANG; Yu LI; Yuxiang FENG (工程科学与技术)
Objective The SPH method is highly effective in handling large deformations and discontinuities in multiphase flow simulations, making it advantageous for modeling complex physical phenomena such as landslide-generated surges. It can more accurately simulate the interactions between landslide surges, terrain, and structures. However, in SPH–based fluid–structure coupling simulations, issues such as particle penetration often occur, particularly in cases involving large-deformation structures, where particle slippage may also present challenges. Consequently, existing studies frequently combine SPH with other techniques, such as the finite element method, to enhance performance. Additionally, the discrete element method cannot achieve fluid-structure coupling. Current research typically employs rigid bodies to simulate the landslide surge process, but no studies have simultaneously modeled the landslide body as a particle system while achieving a complete simulation of the coupling between landslide surges and large-deformation structures.Methods In the calculation process, the interaction between the fluid and the deformable body is initially performed by calculating the particles of the deformable body. Subsequently, the positions are corrected using spring forces. Based on this concept, the SPH method can be improved. In order to validate the accuracy of the proposed SPH method, a dam model test is conducted, utilizing a wave flume experimental setup to simulate surge waves. The experimental equipment measures 40.0 m in length, 0.3 m in width, and 0.3 m in height. The wave generator is driven by an AC servo motor capable of absorbing secondary reflected waves, allowing the simulation of small amplitude waves, solitary waves, and irregular waves. The dam is simulated using M15 micro-particle concrete, with steel reinforcement considered by reducing the modulus of elasticity. A compression test determined the elastic modulus of the dam model to be 70 MPa. The dam measures 20 cm in height, with a bottom width of 5.0 cm and a base width of 37.5 cm, and has a slope angle of 50°. Waterproof fabric is adhered to the model’s periphery and the flume to prevent water leakage around the dam structure.Results and Discussions The improved SPH method can reproduce the entire chain process of landslide collapse, wave generation, structural deformation, and the subsequent disaster sequence. This model, based on a spring-damping method, adjusts the density threshold of particles, effectively addressing penetration issues between solid and fluid particles at boundaries. It also enables the coupling simulation of fluid and structural large deformation. The calculation results of the improved method align well with indoor experimental results. The improved SPH method holds significant engineering application value in simulating the entire dynamic response sequence of landslide-induced waves on structures. Furthermore, the research findings provide technical guidance for emergency prevention and control of major projects affected by landslide-induced waves. By simulating water level changes when waves reach the dam structure, it is demonstrated that as the wave generated by the landslide propagates toward the dam, it swiftly surges, creating a shockwave that induces notable deformation in the dam structure. Subsequently, the wave undergoes fragmentation, leading to a reduction in the dam’s deformation under the effect of the fragmented wave. Afterward, the wave begins to act on the dam structure in the form of a long-period solitary wave. Therefore, in the stability design of dam structures, it is essential to consider the impact of different wave bands on the dam structure to ensure its resilience against potential threats. By analyzing factors such as the distance between the dam and the landslide and the angle of wave impact on the stability of the dam structure, it is found that when the distance between the landslide and the dam increases from 100 to 220 m, the maximum wave force on the dam decreases sharply by approximately 56%. As the distance between the landslide and the dam increases, the intensity of the wave and its force on the dam gradually diminish. Under wave impact, there is an increasing trend in wave pressure from the top to the bottom of the dam, and as the wave impact angle increases, the wave pressure on the dam structure gradually weakens. Significant displacement occurs at the top of the dam due to wave impact, which then gradually decreases. Therefore, in engineering design and disaster emergency processes, resilient measures can be implemented to mitigate the impact of landslide-induced waves, ensuring the safe operation of the dam.Conclusions This study proposes a fluid–solid coupling analysis model based on an improved Smoothed Particle Hydrodynamics (SPH) method. This model employs a spring-damping approach to manage fluid–solid coupling computations in expanding and contracting bodies, effectively resolving issues associated with complex fluid phenomena, large deformation coupling, and inter-particle penetration. Using this approach, the impact response laws of landslide-induced surges on the dam are analyzed.